Nano Differential Scanning Fluorimetry as a Rapid Stability Assessment Tool in the Nanoformulation of Proteins - Sofia Lisina; Wali Inam; Mikko Huhtala; Fadak Howaili; Hongbo Zhang; Jessica M. Rosenholm (MDPI AG, 2023)
The development and production of innovative protein-based therapeutics is a complex and challenging avenue. External conditions such as buffers, solvents, pH, salts, polymers, surfactants, and nanoparticles may affect the stability and integrity of proteins during formulation. In this study, poly (ethylene imine) (PEI) functionalized mesoporous silica nanoparticles (MSNs) were used as a carrier for the model protein bovine serum albumin (BSA). To protect the protein inside MSNs after loading, polymeric encapsulation with poly (sodium 4-styrenesulfonate) (NaPSS) was used to seal the pores. Nano differential scanning fluorimetry (NanoDSF) was used to assess protein thermal stability during the formulation process. The MSN-PEI carrier matrix or conditions used did not destabilize the protein during loading, but the coating polymer NaPSS was incompatible with the NanoDSF technique due to autofluorescence. Thus, another pH-responsive polymer, spermine-modified acetylated dextran (SpAcDEX), was applied as a second coating after NaPSS. It possessed low autofluorescence and was successfully evaluated with the NanoDSF method. Circular dichroism (CD) spectroscopy was used to determine protein integrity in the case of interfering polymers such as NaPSS. Despite this limitation, NanoDSF was found to be a feasible and rapid tool to monitor protein stability during all steps needed to create a viable nanocarrier system for protein delivery.